The geometallurgical framework : Malmberget and Mikheevskoye case studies - Lishchuk, Viktor; Koch, Pierre-Henri; Lund, Cecilia; Lamberg, Pertti (Luleå tekniska universitet, Mineralteknik och metallurgi, 2015)
Geometallurgy is a growing area within a mineral processing industry. It brings together tasks of geologists and mineral processing engineers to do short and medium term production planning. However, it is also striving to deal with long term tasks such as changes in either production flow sheet or considering different scenarios. This paper demonstrates capabilities of geometallurgy through two case studies from perspective of Minerals and Metallurgical Engineering division Lulea University of Technology. A classification system of geometallurgical usages and approaches was developed in order to describe a working framework. A practical meaning of classification system was proved in two case studies: Mikheevskoye (Russia) and Malmberget (Sweden) projects. These case studies, where geometallurgy was applied in a rather systematic way, have shown the amount of work required for moving the project within the geometallurgical framework, which corresponds to shift of the projects location within the geometallurgical classification system. Godkänd; 2015; 20150629 (viklis); Konferensartikel i tidskrift